Complete genome sequence of psychrobacter sp. KFRI-CH2-11: A psychrotolerant bacterium with probiotic, biofortification, and antimicrobial potential for the dairy and meat industriesNCBINCBI - Myunglip Lee; Yucheol Kim; Hae-Won Lee; Yukyoung Park; Sunghun Yi (Data in Brief)
This dataset provides the complete genome sequence of Psychrobacter sp. KFRI-CH2-11, isolated from Korean fermented anchovy, Myeolchi-jeotgal. Genomic analysis identified genes involved in Vitamin B12 biosynthesis, carbohydrate metabolism, CRISPR-Cas defense systems, and antioxidant activity, underscoring the strain's potential for use in food biotechnology. Additional genes linked to antibiotic resistance and bioremediation suggest adaptability in diverse environments, particularly cold-chain storage in the dairy and meat industry. PathogenFinder analysis confirmed the absence of pathogenicity-associated genes, validating the strain's suitability as a probiotic and biofortifying agent in food products.